Electrochemical C−H/N−H Activation by Water‐Tolerant Cobalt Catalysis at Room Temperature. Issue 9 (17th January 2018) - Tian, Cong; Massignan, Leonardo; Meyer, Tjark H.; Ackermann, Lutz
Abstract: Electrochemistry enabled C−H/N−H functionalizations at room temperature by external oxidant‐free cobalt catalysis. Thus, the sustainable cobalt electrocatalysis manifold proceeds with excellent levels of chemoselectivity and positional selectivity, and with ample scope, thus allowing electrochemical C−H activation under exceedingly mild reaction conditions at room temperature in water. Abstract : Electro Co : Cobalt‐catalyzed C−H/N−H functionalizations were accomplished in H2 O at 23 °C without toxic metal oxidants by using electricity. This sustainable cobalt electrocatalysis manifold proceeds with excellent levels of chemoselectivity and positional selectivity, and with ample scope.